Development and Evaluation of a Competitive Enzyme-Linked Immunosorbent Assay Based on Swine Monoclonal Antibodies for Detecting Neutralizing Antibodies against Senecavirus A - Xueqing Ma; Jiaxin Huang; Kun Li; Kailu Ding; Yuanfang Fu; Jing Zhang; Zhixun Zhao; Pinghua Li; Xingwen Bai; Dong Li; Xia Liu; Qiaoying Zeng; et al. (Microbiology Spectrum, 2023)
ABSTRACT Senecavirus A (SVA) is an emerging viral pathogen related to vesicular disease and neonatal mortality in swine, which results in enormous economic losses to the global swine industry. The clinical signs of SVA are indistinguishable from those of other vesicular diseases, such as foot-and-mouth disease, which is an economically devastating animal disease. Therefore, development of a rapid, sensitive, and specific diagnostic method for the detection of SVA infection is critical for the prevention and control of SVA and would help to rule out other exotic diseases. In this study, two whole-porcine anti-SVA antibodies (1M5 and 1M25) were produced using single B cell antibody technology. 1M5 and 1M25 possessed neutralizing activity against SVA but recognized different conformational epitopes that depended on the intact virion. Using 1M5 as the capture antibody and biotinylated 1M25 as the detection antibody, a reliable and rapid competitive enzyme-linked immunosorbent assay for detecting neutralizing antibodies (NAC-ELISA) against SVA was developed. Receiver-operating characteristic curve analysis showed that the sensitivity and specificity of the assay were 98.11% and 100%, respectively, with a cutoff percent inhibition value of 45%. The NAC-ELISA was specific for detecting SVA-specific antibodies, without cross-reactivity to other virus-infected sera. The results of the NAC-ELISA showed a strong agreement with the results of the virus neutralization test. Therefore, the NAC-ELISA developed in this study represents a sensitive, specific, and reliable tool for the detection of SVA-specific antibodies, which is applicable for serodiagnosis and serological surveillance of SVA and is conducive to the prevention and control of SVA. IMPORTANCE Senecavirus A (SVA) is an emerging picornavirus related to vesicular disease and neonatal mortality in swine, which results in enormous economic losses worldwide. Additionally, the clinical characteristics of the disease are indistinguishable from those of other vesicular diseases, such as foot-and-mouth disease. Therefore, developing tools for rapidly and accurately detecting SVA infection is critical and urgent. In this study, two porcine-derived monoclonal antibodies against SVA were generated, and a competitive ELISA for the detection of neutralizing antibodies (NAC-ELISA) against SVA was successfully developed using these two porcine monoclonal antibodies. The NAC-ELISA was SVA specific with no cross-reactivity to other related pathogens and had high sensitivity, specificity, and reproducibility for detecting SVA-specific antibody. Therefore, the NAC-ELISA developed in this study may be of great value as a simple and reliable tool for serodiagnosis or surveillance of SVA and may facilitate the prevention and control of SVA.